The Goal Orientation Theory, learning strategies and academic achievement in secondary students in Lima - Matos-Fernández, Lennia (2006)
To investigate the role of student motivation in the educational context, the Goal Orientation Theory was employed in a sample of 1.505 secondary students in Lima. In the present investigation three types of goals were studied: learning oriented, performance approach and performance avoidance oriented. The empirical evidence is drawn basically from studies with samples of North American middleclass students. Therefore, our objective was to find if this evidence was also valid for a sample of Peruvian students examining the relation among students’ goal orientation, learning strategies and academic performance.